MENAKAR KAPASITAS PESANTREN DI KABUPATEN GOWA - Triana Karyawati (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
The research on mapping of pesantren capacity in Gowa Regency using qualitativemethod, there are three things that want to be inside the mapping, First, about theaccessibility of pesantren geographically, Second, capacity of pesantren asmandated in Ministry of Religion regulation ie: (a) Kiyai or similar mentions; (b)santri; (3) Boarding school (pesantren); (4) Mosque; (5) The Study of OldManuscript of Islam or Islamic Studies with muallimin pattern, while the thirdcapacity is the ability of pesantren in doing empowerment for both santri andpesantren in institutional. The results of this mapping illustrate in general theaccessibility of pesantren in Gowa Regency, the average is far from the capital ofregency, while the fulfillment of the condition of the establishment of pesantren ingeneral has not been fulfilled, empowerment in pesantren focused on agriculture andlivestock is largely gone.